PREPARATION AND EVALUATION OF IBUPROFEN EFFERVESCENT GRANULES - JUTI RANI DEVI; BIDYUT DAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of the present investigation is to prepare the effervescent granules of different formulations and evaluated for different parameters including drug release study. Methods: The effervescent granules of five different formulations such as F1, F2, F3, F4, and F5 were prepared by the wet granulation method using different concentration of excipients including sodium bicarbonate and potassium bicarbonate. The prepared formulations were evaluated for different parameters including effervescent time as well as drug release study. Results: After evaluating all the parameters, it has been found that the formulation F5 shows better drug release among all the formulation and least effervescent time. Where it can conclude that as the effervescent time is less, i.e., it quickly bursts and shows its effect quickly. Lesser the bursting time quicker the drug release.